Drag reduction in aircraft model using Elliptical winglet - Prithvi, Raj Arora, Assoc. Prof. Dr.; A., Hossain; Prasetyo, Edi, Ir.; A. A., Jaafar; Thamir S., Younis; M., Saleem (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/